Pelatihan Pengenalan Aplikasi Editing Video untuk Meningkatkan Keterampilan Digital pada CYNARA'S CORNER dalam Pembuatan Konten - Rahmatika Rahmatika; Nasrulloh Isnain; Ulfa Pauziah (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Marketing a product effectively goes beyond showcasing attractive photos; it involves creating engaging videos that can better explain and demonstrate the products on existing social media platforms. In today’s digital age, maximizing a product's effectiveness through social media marketing is essential. CapCut, a user-friendly video editing application, offers a range of features that enable users to create professional-quality videos easily. These features can be utilized to effectively market a product by conveying its specifications and unique features in a visually compelling way. Recognizing the importance of video content in modern marketing strategies, we organized a training session at Cynara’s Corner, a retailer specializing in children’s and Muslim clothing. This training was designed to teach participants how to utilize CapCut for creating marketing videos. We used the drill and practice method, which involved hands-on exercises to help participants learn how to edit and produce engaging product videos. The training sessions focused on creating videos that could effectively communicate product specifications, such as size, material, and design, in a way that would appeal to potential buyers. These videos, once created, would be shared on social media platforms to provide comprehensive and informative content to attract potential customers. The training aimed to equip participants with the skills necessary to produce engaging content that would increase product visibility and appeal. By the end of the training, the participants were able to create professional videos that could be used for social media marketing. These videos not only showcased the products but also provided valuable information to help customers make informed purchasing decisions. This initiative will enable Cynara’s Corner to strengthen its social media presence and ultimately boost its sales by engaging potential buyers more effectively through creative video content.